2023
DOI: 10.1002/etc.5770
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Growth, and Reproduction Responses in a Three‐Generation Exposure of the Zebrafish (Danio rerio) to Perfluorooctane Sulfonate

Kurt A. Gust,
J. Erik Mylroie,
Ashley N. Kimble
et al.

Abstract: A prior multigenerational perfluorooctane sulfonic acid (PFOS) exposure investigation in zebrafish reported adverse effects at 0.734 µg/L, among the lowest aquatic effect levels for PFOS reported to date. The present three‐generation PFOS exposure quantified survival, growth, reproduction, and vitellogenin (VTG; egg yolk protein) responses in zebrafish, incorporating experimental design and procedural improvements relative to the earlier study. Exposures targeting 0.1, 0.6, 3.2, 20, and 100 µg/L in parental (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The study herein contributes to the knowledge gap by characterizing growth and survival impacts of PFOS at a critical life stage. Furthermore, it continues extensive PFOS research in our laboratory and it was recently suggested that fish testing methodologies may have substantial impacts on regulatory values for PFAS (Krupa et al 2022 ; Gust et al 2023 ).…”
mentioning
confidence: 98%
“…The study herein contributes to the knowledge gap by characterizing growth and survival impacts of PFOS at a critical life stage. Furthermore, it continues extensive PFOS research in our laboratory and it was recently suggested that fish testing methodologies may have substantial impacts on regulatory values for PFAS (Krupa et al 2022 ; Gust et al 2023 ).…”
mentioning
confidence: 98%